2001
DOI: 10.1046/j.1365-2982.2001.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Contractile effects and intracellular Ca2+ signalling induced by motilin and erythromycin in the circular smooth muscle of human colon

Abstract: Motilin has excitatory effects on the colon of the rabbit and the dog, but little is known of its effect on the human colon. The aim of this study was to investigate the effects induced by motilin and erythromycin A (EMA) on muscle strips and on single cells from primary cultures from human colon. Isotonic contraction was recorded in circular muscle strips from macroscopically normal resection specimens of patients operated on for colonic neoplasm. Agonist-induced intracellular Ca2+ ([Ca2+]i) signalling was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 30 publications
5
44
0
1
Order By: Relevance
“…Motilin-induced PI hydrolysis was concentration dependent and paralleled motilin-induced contraction (2). In cultured, human colonic smooth muscle cells loaded with indomethacin-1, motilin caused an increase in cytosolic free Ca 2ϩ { [Ca 2ϩ ] i }, consistent with inositol 1,4,5-trisphosphate (IP 3 )-dependent Ca 2ϩ release (35). Motilin-induced increase in [Ca 2ϩ ] i in the human medulloblastoma cell line TE671, which express motilin receptors, was retained in Ca 2ϩ -free medium or the presence of the Ca 2ϩ channel blocker nifedipine (32).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Motilin-induced PI hydrolysis was concentration dependent and paralleled motilin-induced contraction (2). In cultured, human colonic smooth muscle cells loaded with indomethacin-1, motilin caused an increase in cytosolic free Ca 2ϩ { [Ca 2ϩ ] i }, consistent with inositol 1,4,5-trisphosphate (IP 3 )-dependent Ca 2ϩ release (35). Motilin-induced increase in [Ca 2ϩ ] i in the human medulloblastoma cell line TE671, which express motilin receptors, was retained in Ca 2ϩ -free medium or the presence of the Ca 2ϩ channel blocker nifedipine (32).…”
mentioning
confidence: 70%
“…A number of previous studies have shown that motilin receptors are present in smooth muscle cells derived from various regions of the gut (stomach, small intestine, colon, gallbladder) in different species (human, dog, rat, and guinea pig) (2,5,7,15,30,35 (24), and LPA 3 (39) receptors, all of which stimulate PI hydrolysis by activating PLC-␤1 via G␣ q .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest frequency was found in nerve fractions of antrum, but also binding sites in duodenum and colon were detected, while there were no receptors demonstrated in ileum and jejunum. [15][16][17] Due to the species differences it is important that more studies are performed on motilin receptor expression in human intestine. A few years ago an orphan human G-protein receptor (GPR38-A) was identified as a motilin receptor 18 and more techniques became available to detect this motilin receptor.…”
mentioning
confidence: 99%
“…De todo modo, o efeito procinético da motilina está bem estabelecido, embora não esteja definida sua atividade no cólon 17,18,19,20,21,22,23 . Constituímos quatro grupos de 15 pacientes: a) controle: nuligestas; b) primigestas no 1º trimestre; c) 2º trimestre; d) 3º trimestre.…”
Section: Introductionunclassified